2016
DOI: 10.1002/chem.201604991
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Catalyzed Hydrogenation of Esters to Alcohols

Abstract: Homogeneous catalytic hydrogenation of esters to alcohols is an industrially important, environmentally benign reaction. While precious metal-based catalysts for this reaction are now well known, only very few catalysts based on first-row metal complexes were reported. Here we present the hydrogenation of esters catalyzed by a complex of earth-abundant manganese. The reaction proceeds under mild conditions and insight into the mechanism is provided based on an NMR study and the synthesis of novel Mn complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(79 citation statements)
references
References 52 publications
1
78
0
Order By: Relevance
“…[14] When ac atalytic reaction was performed under the conditions described for entry 2 ( Table 1) using the independently isolated complex 2,complete conversion of diethyl carbonate to ethanol and methanol in more than 90 %y ield was observed, indicating that complex 2 is an active catalytic species in the hydrogenation of carbonates.Inpresence of H 2 , complex 2 immediately forms the hydride complex 3 as previously reported by us. We have previously shown that complex 2 is an active catalyst for the hydrogenation of esters.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations
“…[14] When ac atalytic reaction was performed under the conditions described for entry 2 ( Table 1) using the independently isolated complex 2,complete conversion of diethyl carbonate to ethanol and methanol in more than 90 %y ield was observed, indicating that complex 2 is an active catalytic species in the hydrogenation of carbonates.Inpresence of H 2 , complex 2 immediately forms the hydride complex 3 as previously reported by us. We have previously shown that complex 2 is an active catalyst for the hydrogenation of esters.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[14] Complex 1 was also used by us for the direct synthesis of cyclic imides by dehydrogenative coupling of diols and amines. [14] Complex 1 was also used by us for the direct synthesis of cyclic imides by dehydrogenative coupling of diols and amines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Them ild reaction conditions tolerated fluoride,t hioether, ether, amine,a nd benzyl substituents.T risubstituted alkenes were quantitatively converted at 10 bar H 2 and 60 8 8C( entries [19][20][21][22][23][24]. Them ild reaction conditions tolerated fluoride,t hioether, ether, amine,a nd benzyl substituents.T risubstituted alkenes were quantitatively converted at 10 bar H 2 and 60 8 8C( entries [19][20][21][22][23][24].…”
Section: Zuschriftenmentioning
confidence: 99%
“…[16] Theu se of inexpensive,a bundant, and non-toxic base metals has only recently been evaluated in the context of hydrogenations. [18] In the past three years,only ahandful of homogeneous pincer-type Mn complexes were applied to hydrogenations of polar C = Xb onds,s uch as carbonyl and nitrile compounds as well as carbon dioxide,bythe groups of Beller, [19] Kempe, [20] Milstein, [21] and others. [18] In the past three years,only ahandful of homogeneous pincer-type Mn complexes were applied to hydrogenations of polar C = Xb onds,s uch as carbonyl and nitrile compounds as well as carbon dioxide,bythe groups of Beller, [19] Kempe, [20] Milstein, [21] and others.…”
mentioning
confidence: 99%